Seismic Tomography of the Trans-North China Orogen and Its Dynamic Implications - Xu, Xiaoming; Ding, Zhifeng; Guo, Huili; Li, Xinfu (Frontiers in Earth Science, 2022)
We present a high-resolution S wave velocity model of the Trans-North China Orogen (TNCO) and its adjacent areas derived from S wave traveltime residuals of teleseismic waveforms recorded by the dense ChinArray seismic network. Our model reveals S wave velocity anomalies beneath the study area, suggesting the strong lateral heterogeneities of the upper mantle structures. The upper mantle of the Datong volcano is dominated by the significant low velocity anomalies. In addition to the low-velocity zone rooted in the mantle transition zone beneath the Datong volcano region, two low velocity layers extend northwestward to the Hetao graben and southwestward to the southern TNCO within depths of 100-300 km, respectively. Based on these low-velocity anomalies, we provide new insights into the origin of the Datong volcano, which may be related to the asthenospheric upwelling originated from the water-rich mantle transition zone and horizontal mantle flows driven by the extrusion northeastward of the Tibetan plateau. A clear velocity contrast in the upper mantle above 300 km depth beneath the Ordos block and the TNCO implies that the Ordos block still preserves thick cratonic root while the lithosphere of the TNCO is modified. We propose that the asthenospheric upwelling and northeastward push of the Tibetan plateau account for the lithospheric deformation of the TNCO and its adjacent areas.